A transcranial magnetic stimulation study on response activation and selection in spatial conflict. (12th December 2014) - Bardi, Lara; Schiff, Sami; Basso, Demis; Mapelli, Daniela
Abstract In choice reaction tasks, subjects typically respond faster when the relative spatial positions of stimulus and response correspond than when they do not, even when spatial information is irrelevant to the task (e.g. in the Simon task). Cognitive models attribute the Simon effect to automatic response activation elicited by spatial information, which facilitates or competes with the controlled selection of the correct response as required by task demands. In the present study, we investigated the role of the dorsal premotor cortex (PMd) in response activation and selection during spatial conflict. We applied single‐pulse transcranial magnetic stimulation (TMS) to the PMd of the right and left hemispheres during the execution of a Simon task, at different times after the onset of the visual stimulus. The results showed that TMS produced a different effect on subjects' performance in two separate time windows. When TMS was applied at an early time [160‐ms stimulus onset asynchrony (SOA)], we observed suppression of the Simon effect, resulting from a delay of corresponding trials. When TMS was applied at a late time (220 and 250‐ms SOA), we observed an increase in the Simon effect, resulting from a delay of non‐corresponding trials. These outcomes revealed that the PMd is involved both in the activation of the spatially triggered response and in response selection during spatial conflict.